Manajemen Komunikasi Organisasi Pada Ikatan Pelajar Nahdlatul Ulama (Ipnu) Kota Jakarta Selatan Di Era Pandemi Covid-19 - Syavira Aulia; Ahmad Toni (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The Nahdlatul Ulama Student Association or IPNU is an organization that accommodates students under the auspices of Nahdlatul Ulma to form youth in accordance with the Islamic faith. During the COVID-19 pandemic, all human activities changed, including the organizational activities of IPNU South Jakarta. The health protocols required by the government are different from those that were used before the COVID-19 pandemic. This study aims to analyze how the organizational communication process occurred at IPNU South Jakarta after the COVID-19 pandemic. The research theory is organization communication. The research method used in this research is descriptive qualitative with interview data collection and literature study. The results showed that there were significant changes in the IPNU South Jakarta organization after the covid-19 pandemic. Communication is carried out online, the use of social media is maximized, soft skills development is carried out online, and visits to outside the region are temporarily suspended. These changes can be handled properly because of good communication management at IPNU South Jakarta so that the planned work program can run optimally.